ENT 530 Social Media Portfolio / Nurhayati Mohd Sharif - Mohd Sharif, Nurhayati (2019)
The brownie, one of America's favorite baked treats, was born in the U.S.A. Even though it is a relatively recent entry to the food pantheon, the recipe first appeared in print in the early 20th century, there is no smoking gun. Evidence points to Fanny Farmer, who, in 1905, adapted her chocolate cookie recipe to a bar cookie baked in a rectangular pan. (The brownie is classified as a bar cookie rather than a cake. That is because brownies are finger food, like cookies, and cake is eaten with a fork). There are thousands of recipes, both "cake" types and "fudge" types. Either is perfectly correct and delicious. It's easy to see that the brownie got its name from its dark brown color. Here is more about the style of brownies. There are numerous legends surrounding the origin of the brownie. The legend is told variously: a chef mistakenly added melted chocolate to a batch of biscuits, a cook was making a cake but didn't have enough flour. Brownies cookies is popular among Malaysian citizen. This is because brownies cookies are rich flavor with chocolate and also crunchy. Target market for brownies cookies is for student, family and friends. Nowadays, people like to buy brownies cookies for their door gift in their event. It easier to packaging and can long lasting about two to three month. In addition, the market segmentation of this product come from demographic and geographic. The customer can place the order through what's app and also personal message through Facebook page. The location that cover for delivery is only in the UiTM Puncak Alam, Selangor. Chip Chip Brownies Cheap has one owner and under the sole proprietorship business. All the budget and profit come from the owner and the owner is responsible for their business.